2015
DOI: 10.17016/feds.2015.080
|View full text |Cite
|
Sign up to set email alerts
|

Venture Capital and the Performance of Incumbents

Abstract: I study the effect of investment in young, private firms by venture capitalists (VC) on public firms in the same industry. I construct an instrument for VC investment that relies on individual VC's investment histories, holdings of equity stakes in IPO firms, and aggregate market returns immediately following those IPOs. I find that increased VC investment has a large effect on incumbent profitability.The effect arises due to higher costs and not depressed sales. The effect is short lived as firms respond by r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…Chod and Lyandres (2011) showed that a firm's IPO affects the value of their rivals' products negatively. Dore (2015) related a firm´s increase in equity with the negative returns of its rivals. He argued that the effects are due to an increase in costs and not a decrease in revenues.…”
Section: Explaining the Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Chod and Lyandres (2011) showed that a firm's IPO affects the value of their rivals' products negatively. Dore (2015) related a firm´s increase in equity with the negative returns of its rivals. He argued that the effects are due to an increase in costs and not a decrease in revenues.…”
Section: Explaining the Resultsmentioning
confidence: 99%
“…Recently, Dore (2015) linked the increase of equity (positive share supply shock) with rivals' negative returns. He showed that venture capital investment in small private firms provoked a negative effect on the returns of their publicly traded rivals.…”
Section: Competitive and Contagion Effectsmentioning
confidence: 99%